Attentive Groupware - Ferreira, António (2009)
In this paper we present a combined perspective over groupware and attentive user interfaces. The problem that we address is how to attenuate the distracting effects of the multiple interruptions that characterize computer-mediated collaboration, while maintaining the necessary notion of group awareness. We introduce a framework of group attention consisting of collaboration facets, information flows, and attentive devices. Based on known psychological factors we propose four such devices: the time separator, the opportunity seeker, the change emphasizer, and the activity anticipator. Finally, we demonstrate the framework role in the design of an electronic brainstorming tool.